RNA interference and turnover in plants -a complex partnership - Krzyszton, Michal; Kufel, Joanna; Zakrzewska-Placzek, Monika (Frontiers in Plant Science, 2025)
Plants, often exposed to unfavorable external conditions and pathogen attacks, have developed a remarkably complex network of RNA interference (RNAi) pathways. This allows them to adapt gene expression to environmental cues and protects their genomes from invading nucleic acids. The process involves the production of small RNA molecules (sRNAs), which are crucial for ensuring the specificity of this mechanism and ultimately inhibiting the progression of viral infections or the movement of transposons within the genome. The generation of sRNAs is closely linked and balanced with mRNA turnover, as key stages of mRNA synthesis, such as 5’-capping, mRNA maturation, and transcription termination, affect sRNA generation and RNA silencing. Since there are many reviews available on sRNA biogenesis and function, we focused on summarizing the connections between RNA silencing and turnover, explaining how defective RNA maturation or degradation triggers RNA interference. Importantly, RNAi has gained attention as a promising strategy for developing innovative pest control techniques, leveraging this biological mechanism to protect crops. Nonetheless, how the expression of exogenous small RNAs in plants affects the relationship between small RNA and mRNA turnover, as well as how these RNAs are incorporated into specific RNAi pathways, remains uncertain.